(untitled) (Fiep Bulletin - online, 2011)
Introduction: Sacro-iliac Dysfunction (DSI) is a term used to characterize the anatomical positioning biomechanical abnormalities in one or both sacroiliac joints (ASI). The aim of this study was to identify possible dysfunctions of the sacroiliac joints, analyze the rearfoot plantar pressure through baropodometry before and after handling, and treat disorders of the sacroiliac joints evaluated and detected. Promoting improvement of pelvic mobility through therapy osteopathic manipulative (TOM). Methods: The sample comprised 50 students from the State University of West of Paraná, campus of Cascavel. We conducted tests to diagnose specific orthopedic ISD being: Gillet test (AV1) and Test Downing (AVD1). Found some fixing in ASI, the patient was assessed with Baropodometry (BARO 1) which found in the rearfoot plantar pressure. Then there was the manipulation technique called the Direct Iliac (TDI), reassessing the iliac right after them with the Gillet test (AV2) to validate or not the return of the biomechanics of the joint. Were reassessed Baropodometric (BARO 2) to verify the rearfoot plantar pressure after manipulation. Results: The prevalence of type and hand dysfunction was 57% of the left anterior dysfunction (DEA), 27% of anterior right ventricular dysfunction (ADI), 10% of the left posterior dysfunction (DEP) and 6% of right posterior dysfunction (DDP). Regarding the prevalence of dislocation after manipulation of the iliac, 47% shifted to earlier, 29% and 24% for later remained the same or not significantly different (> 3%). Verified the effectiveness of manipulation of the iliac as it returned to 100% of the patients mobility sacroiliac immediately. Conclusion: The bearing hind foot after manipulation of the iliac decreased, but the results were not statistically significant.